Determination of microbial community in a pilot scale two-stage step-feed biological nutrient removal process - Demir, Manav N.; Debik, E.; Ozkaya, B.; Coskun, T. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2019)
Microbial community was determined in a pilot-scale two-stage step-feed biological nutrient removal system treating municipal wastewater with 10 m(3) d(-1) capacity. Grit chamber effluent at Istanbul Atakoy Biological Wastewater Treatment Plant was used as influent wastewater. In the pilot plant, the influent wastewater was split into two fractions to anaerobic and anoxic2 tank. Nitrosomonas, Nitrosospira, Accumulibacter, and Dechloromonas along with some other uncultured microorganisms were determined in the aerobic, anoxic and anaerobic stages. COD, TN, NH4+-N, TP, PO43--P, SS, and VSS removal efficiencies were found to be 86.7%, 80.3%, 92.5%, 89.5%, 87.5%, 94.8%, and 95.0% in average, respectively, at 5000 mg MLSS L-1, 15 days of SRT and 16 hours of HRT. The results indicated that microbial community in the process was quite similar with those in the nutrient removal processes with no step feeding. This process can be used cost-effectively to remove carbon and nutrients from medium-strength municipal wastewaters.
Keywords: Biological nutrient removal; step feeding; municipal wastewater; microbial community; PCR-DGGE; WASTE-WATER TREATMENT; AMMONIA-OXIDIZING BACTERIA; SEWAGE-TREATMENT PLANTS; PHOSPHORUS REMOVAL; ACTIVATED-SLUDGE; NITROGEN REMOVAL; NITRIFICATION PERFORMANCE; MEMBRANE BIOREACTOR; MUNICIPAL; CARBON; Environmental Sciences & Ecology